Guillain-Barré syndrome as a paraneoplastic manifestation of disseminated squamous cell carcinoma. (31st May 2013) - Navani, Vishal; Webster, Daniel; Williams, Sion K; Agranoff, Daniel
Abstract : We describe a 65-year-old woman who developed ascending, symmetrical paraesthesia and weakness. This was on a background of metastatic disseminated squamous cell carcinoma, with a likely recurrent mandibular primary. Serum testing for antiganglioside antibodies was strongly positive. Despite a 5-day course of intravenous immunoglobulin, the patient passed away on day 34 of admission. This is the first case, to our knowledge, of Guillain-Barré syndrome in association with squamous cell carcimoma.